2012
DOI: 10.1111/j.1532-849x.2012.00927.x
|View full text |Cite
|
Sign up to set email alerts
|

Complete Denture Occlusion: An Evidence‐Based Approach

Abstract: The article is associated with the American College of Prosthodontists' journal-based continuing education program. It is accompanied by an online continuing education activity worth 1 credit. Please visit www.wileyonlinelearning.com/jopr to complete the activity and earn credit. KeywordsBilateral balanced occlusion; canine guidance; conventional complete denture. Correspondence AbstractPurpose: This study involved an extensive search for randomized controlled clinical trials comparing bilateral balanced and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 10 publications
0
25
1
2
Order By: Relevance
“…[9][10][11][12][13] To date, unbalanced occlusions such as canine guidance and balanced occlusions such as fully bilateral balanced occlusion (FBBO), linear or zero-degree monoplane posterior scheme, lingualised occlusion (LO) and buccalised occlusion (BO) have been suggested and their efficacy has been investigated for CCDs. 2,7,8,13 Almost all previous studies have acknowledged that balanced occlusion is a prerequisite for appropriate prosthetic rehabilitation 2,7,8 except one study that rejected this belief. 11 Most previous studies reported lower patient satisfaction rate, less favourable aesthetics and lower masticatory function for monoplane occlusion, 7,9,10,14 and more problems were reported for FBBO compared to LO and BO.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] To date, unbalanced occlusions such as canine guidance and balanced occlusions such as fully bilateral balanced occlusion (FBBO), linear or zero-degree monoplane posterior scheme, lingualised occlusion (LO) and buccalised occlusion (BO) have been suggested and their efficacy has been investigated for CCDs. 2,7,8,13 Almost all previous studies have acknowledged that balanced occlusion is a prerequisite for appropriate prosthetic rehabilitation 2,7,8 except one study that rejected this belief. 11 Most previous studies reported lower patient satisfaction rate, less favourable aesthetics and lower masticatory function for monoplane occlusion, 7,9,10,14 and more problems were reported for FBBO compared to LO and BO.…”
Section: Introductionmentioning
confidence: 99%
“…While canine guidance has not been recommended by prosthodontists as an occlusal scheme for complete dentures, studies have shown little difference in patient satisfaction between groups of patients having complete dentures with either canine guidance or balanced occlusion (Hey decke et al 2008, Paleari et al 2012, FariasNeto & Carreiro 2013. Canine guidance is commonly present in the natural dentition of young patients; however, throughout life attrition of the natural dentition generally leads to the establishment of a unilateral group function.…”
Section: Canine Guidancementioning
confidence: 99%
“…When examining the true advantage of bilateral balanced tooth set up there was no detectable advantage functionally in the majority of studies examined in a systematic review [39].…”
Section: Occlusion and The Ageing Patientmentioning
confidence: 99%